ADAB PERGAULAN ANTARA PENDIDIK DAN PESERTA DIDIK (KAJIAN KITAB IHYA ULUM AL-DIN KARYA IMAM ABU HAMID MUHAMMAD BIN MUHAMMAD BIN MUHAMMAD AL-GHAZALI): AL-GHAZALI`S BOOK IHYA ULUM AL-DIN STUDY - Zubaidah (Institut Agama Islam Darul Ulum Kandangan, 2023)
This study aims to describe and analyze the ethics of interaction between teacher and student according to the perspective of Imam Al-Ghazali in the book Ihya Ulum Al-Din to develop the concept of interaction ethics in the field of education and as an effort to form the next generation of students. People who have morals according to educational goals. This study uses a qualitative descriptive approach and the type of research used is literature. Data collection technique searches for data about objects or variables in the form of notes, journals, books, etc. The data is collected in the form of written notes/data, meanwhile, the data analysis used is content analysis. In this study, it was extracted from the results of the study, after tracing its traces from the book Ihya Ulum Al-Din, it was found that the ethics of interaction between teacher and student according to Imam Al-Ghazali: The teacher must sympathize with the students, imitate, imitate the nature of the Prophet Muhammad in the performance of his educational duties, and he intended to seek Please God Almighty. While the ethics of the student’s interaction with teachers according to Imam Al-Ghazali: The student must purify his soul from vile qualities before studying, so that the knowledge that he will learn is useful and rooted in his soul; And in seeking knowledge, only hope is for the pleasure of God Almighty.